Measurement of Wγ and Zγ production cross sections in pp collisions at √s=7 TeV and limits on anomalous triple gauge couplings with the ATLAS detector* - Aad, Georges; Anders, Gabriel; Anders, Christoph; Andrei, George Victor; Davygora, Yuriy; Dietzsch, Thorsten; Geweniger, Christoph; Hanke, Paul; Henke, Michael; Kasieczka, Gregor; Khomich, Andrei; Kluge, Eike-Erik; et al. (Physics letters, 2012)
This Letter presents measurements of l±νγ and l+l−γ (l=e,μ) production in 1.02 fb−1 of pp collision data recorded at s=7 TeV with the ATLAS detector at the LHC in the first half of 2011. Events dominated by Wγ and Zγ production with leptonic decays of the W and Z bosons are selected, and their production cross sections and kinematic properties are measured in several ranges of the photon transverse energy. The results are compared to Standard Model predictions and are used to determine limits on anomalous WWγ and ZZγ/Zγγ couplings.
ATLAS Collaboration: G. Aad, C.F. Anders, G. Anders, V. Andrei, Y. Davygora, T.A. Dietzsch, C. Geweniger, P. Hanke, M. Henke, G. Kasieczka, A. Khomich, E.-E. Kluge, A. Kugel, R. Maenner, K. Meier, F. Müller, R. Narayan, S. Poddar, S. Schaetzel, V. Scharf, A. Schöning, S. Schmitt, N. Schroer, H.-C. Schultz-Coulon, R. Stamen, M. Wessels [und weitere]
Gesehen am 28.11.2018